Identification of molecular markers for type 2 Diabetes mellitus in Sidoarjo, Indonesia - Mushlih, Miftahul; Sari, Fitri Kumala; Amin, Hindah Sabrina; Iknan, Siti Asriani (POLTEKKES KEMENKES YOGYAKARTA, 2020)
T2DM can be triggered by two collaborating factors, namely genetics and the environment. This study aimed to identify genetic markers that can be used to detect the possibility of a person having T2D using the random amplified polymorphism DNA (RAPD) method. The study was carried out cross-sectional and involved 60 samples consisting of 30 positive T2D samples and 30 negative samples T2D. The primer used for PCR-RAPD was D20 (5'-ACCCGGTCAC-3’). The PCR-RAPD results were then analyzed using the scoring method and analyzed using the non-parametric Chi-Square test (cl: 95%). Among T2D, 576 bp band were confirmed to be markers in the patients.